A link between high-speed solar wind streams and explosive extratropical cyclones. (November 2016) - Prikryl, Paul; Iwao, Koki; Muldrew, Donald B.; Rušin, Vojto; Rybanský, Milan; Bruntz, Robert
Abstract: A link between solar wind magnetic sector boundary (heliospheric current sheet) crossings by the Earth and the upper-level tropospheric vorticity was discovered in the 1970s. These results have been later confirmed but the proposed mechanisms remain controversial. Extratropical-cyclone tracks obtained from two meteorological reanalysis datasets are used in superposed epoch analysis of time series of solar wind plasma parameters and green coronal emission line intensity. The time series are keyed to times of maximum growth of explosively developing extratropical cyclones in the winter season. The new statistical evidence corroborates the previously published results (Prikryl et al., 2009). This evidence shows that explosive extratropical cyclones tend to occur after arrivals of solar wind disturbances such as high-speed solar wind streams from coronal holes when large amplitude magneto-hydrodynamic waves couple to the magnetosphere-ionosphere system. These MHD waves modulate Joule heating and/or Lorentz forcing of the high-latitude thermosphere generating medium-scale atmospheric gravity waves that propagate energy upward and downward from auroral zone through the atmosphere. At the tropospheric level, in spite of significantly reduced amplitudes, these gravity waves can provide a lift of unstable air to release the moist symmetric instability thus initiating slantwise convection and forming cloud/precipitation bands. The release of latent heat is known to provide energy for rapid development and intensification of extratropical cyclones. Highlights: Extratropical cyclone tracks are obtained from the JRA-25 and ERA-40 re-analyses. Explosive extratropical cyclones tend to occur after arrivals high-speed solar wind streams. Auroral gravity waves may play a role in the release of instabilities leading to storms.